Analysis of the effects of underground storey supplementation of multiple excavation methods under different foundation forms - He, Xiaotong; Zhong, Zhibin; Li, Wei; Zheng, Yongli; Huang, Shangheng; Liu, Baoxian; Shu, Zhile; Li, Tao; Li, Jie (Frontiers in Built Environment, 2025)
Given the acceleration of urbanisation processes, urban lands have nearly become saturated, and the gap between population and land is increasing. The development of underground spaces has become important for solving the three major crises of urban population, resources, and environment and is a critical step in the sustainable development of cities. Therefore, the effects of the excavation method and drag-and-replace on underground storey supplementation of 3 × 3 frame structures having different foundations were investigated in this study through model tests and numerical simulations. The results show that removal of the top slab in the concentric square slab tray replacement produces the most unfavourable working conditions when the foundation is independent. In cruciform slab draglines, uneven settlement of the non-equal-span frame structures is greater than that of equal-span frame structures, and the final settlement is positively correlated with the span size. The central shaft and surround-island-type soil excavation methods are more effective when applied to free-standing foundations. Deformation of the strip foundation in the pile-wall type of buttress is mainly concentrated in the contact area with the buttress pile and middle area of the frame. The ring-shaped reserved core soil body earth excavation method is more effective for layered excavation in the buttressing of strip foundation piles. Based on these findings, corresponding measures are proposed for use as project references.